Education and HIV/AIDS : A Sourcebook of HIV/AIDS Prevention Programs - World Bank (Washington, DC, 2013)
This sourcebook aims to support efforts by countries to strengthen the role of the education sector in the prevention of HIV/AIDS. It was developed in response to numerous requests for a simple forum to help countries share their practical experiences of designing and implementing programs that are targeted at school-age children. The sourcebook seeks to fulfill this role by providing concise summaries of programs, using a standard format that highlights the main elements of the programs and makes it easier to compare the programs with each other. All the programs are summarized in section two, which allows those seeking advice on program design to browse through the various options and identify those that might reward further study. The full program reports for each country are given in section three. Each program report follows the same format, so the reader can more easily find those aspects of the program that are of specific interest. The consistent design also allows for ease of comparison between programs. There are four main sections within each full program report. Part A gives an overview of the program, describing the rationale, the aims and objectives, the target audience, the components, and the main approaches. Part B describes the process from the initial needs assessment, through the development of materials and training, to the practical details of implementation. There is an attempt made to estimate unit costs, but these should be seen only as indicative, because the number of beneficiaries is often uncertain and because costs in newly implemented programs may be artificially high. Part C provides an assessment and comprises lessons learned. This section begins with comments from implementers on the challenges faced and the lessons learned, followed in a few cases by a description of any formal evaluation of the program. The final part explores the extent to which the program complies with a set of benchmarks that, on the basis of expert opinion, contribute to an effective program. Part D gives details of the organizations involved with the program, including their contact information. It lists all the materials that are available to the reader, along with an order code number.